Air curtain application in a purged unified pod. (25th January 2017) - Hu, Shih-Cheng; Lin, Tee; Fu, Ben-Ran; Wang, Tian-Yi
Highlights: Using purge method or air curtain to prevent moisture into a FOUP was investigated. Moisture prevention performances for two methods were completely contradictory. Using diffuser purge with air curtain is a promising method to moisture prevention. Abstract: The removal or prevention of contaminations (such as particle, oxygen, and moisture) on the wafer during fabrication and transportation is critical. For example, moisture and oxygen cause Cu oxidation and damage during wafer waiting in a portable container. This study employs an air curtain to prevent moisture entering into a purged front-opening unified-pod (FOUP; a container for the storage of wafers) when its door is opened in a minienvironment. The experimental results demonstrate that a better moisture prevention performance was achieved near the lower regions of the FOUP by using the diffuser purging method, whereas near its upper regions, better moisture prevention was achieved when the air curtain was applied. In addition, the results reveal that the use of both diffuser purge and air curtain might be a promising approach to moisture prevention. The present findings can be useful for practical application in semiconductor manufacturing processes.